Antioxidant activity in vivo and biological safety evaluation of a novel antioxidant peptide from bovine hair hydrolysates. (May 2017) - Zeng, Wei-Cai; Sun, Qun; Zhang, Wen-Hua; Liao, Xue-Pin; Shi, Bi
Graphical abstract: Highlights: BHP showed the strong ability to enhance the activities of antioxidant enymes. BHP could decrease the malondialdehyde level in animal serums effectively. BHP exhibited no obvious acute toxicity and genetics toxicity. Abstract: The antioxidant activity in vivo and biological safety of a novel antioxidant peptide from bovine hair hydrolysates (BHP) were investigated. In various testing systems, BHP showed a strong capability to enhance the activities of antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px). Moreover, BHP led to a significant decrease of malondialdehyde (MDA) level in animal serums. All the results indicated that BHP (with a major sequence of Cys-Glu-Arg-Pro-Thr-Cys-Cys-Glu-His-Ser) had a remarkable antioxidant activity in vivo . Meanwhile, no mortalities or evidence of adverse effects was observed in Sprague-Dawley rats following acute oral gavage with BHP at a dose of 10 g/kg body weight during the acute toxicity test. Furthermore, the negative results obtained in Ames test, bone marrow micronucleus test and sperm malformation test demonstrated that BHP had no obvious genetic toxicity to cause mutagenicity of microorganism gene, chromosome and genital cells. All the results suggested that BHP possessed the remarkable antioxidant activity in vivo and biological safety, and therefore had the potential value to be safely utilized as a natural antioxidant agent applied in pharmaceutical, cosmetic and medicinal industries.